Curcumin inhibits the migration of osteoclast precursors and osteoclastogenesis by repressing CCL3 production - Zhengeng Liang; Yan Xue; Tao Wang; Qi Xie; Jiafu Lin; Yu Wang (BMC, 2020)
Abstract Background Curcumin can inhibit the osteoclastogenesis and the migration of several cells including macrophages. Osteoclast precursors (OCPs) are known to exist as bone marrow-derived macrophages (BMMs). This study aims to explore whether curcumin can prevent the fusion and differentiation of OCPs to mature osteoclasts by inhibiting OCP migration. Methods In this study, we investigated the role of curcumin in regulating the production of several chemokines (CCL2, CCL3 and CX3CL1) and the migration of OCPs by ELISA, Western blotting and Transwell assays. Furthermore, we explored the role of curcumin in the chemokines-related osteoclastogenesis using pharmacological intervention and virus infection, and used ovariectomized (OVX) mice (osteoporosis model) to explore the effect of curcumin on the production of specific chemokine in vivo. Results The results showed that curcumin significantly reduced the production of CCL3 in OCPs. Moreover, curcumin-inhibited the migration of OCPs was not affected by CCR1 (Receptor of CCL3) overexpression. Remarkably, curcumin-reduced osteoclastogenesis was significantly reversed by CCL3 addition, while CCR1 overexpression did not increase the osteoclastogenesis in the presence of curcumin. Furthermore, in vivo assays also showed that curcumin significantly reduced the production of CCL3 in OCPs in the trabecular bone of OVX mice. Conclusions In conclusion, curcumin prevents the migration of OCPs by reducing CCL3 production, ultimately inhibiting the formation of mature osteoclasts. Therefore, our study provides the clues for improving the clinical strategies of osteoporosis, dental implantation or orthodontic treatment.